Growth and Yield of Moringa Plants (Moringa oleifera Lam.) in Types of Soil With Different of Fertilizer TSP and Urea - I M. P., Adhi; Kusumawati, N. N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2019)
interaction between soil types with different doses of TSP and urea fertilizer. This research was conducted for 7 weeks in Sading Village, Kec. Mengwi, Kab. Badung. The design used in this study is a completely randomized design (CRD) factorial pattern of two factors. The first factor was soil type (regosol, latosol and mediterrane), and the second factor was dosage fertilizer namely D1 (urea 100 kg/ha); D2 (urea 50 kg/ha + TSP 50 kg/ha), and D3 (TSP 100 kg/ha). In this study, there were 9 treatment combinations that were repeated four times so that there were 36 research pots. The results showed no interaction between soil types with different TSP and urea fertilizer doses, on all growth variables, yields and growth characteristics. Moringa plant growth and yields planted on regosol, latosol and mediterran soil types yielded non significant different results on all growth variables, yields and, growth characteristics. Giving different doses of TSP and urea fertilizer, showed no significant different results on all growth variables, yields, and growth characteristics of Moringa plants. It can be concluded that the growth and yield of Moringa plants tend to be the best in regosol soil types, whereas in the treatment of 50 kg fertilizer TSP/ha + 50 kg urea/ha tend to give the best moringa plant yields. There was no interaction between soil type and fertilizer dosage on the growth and yield of Moringa plants.   Keywords : plant moringa, growth, yield, type of soil, TSP, urea